The mined mass measurement by using drone technology approach in the local scale mining in Tumiyang area, Kebasen District, Banyumas Regency, Central Java, the observation area of CV. Sinergi Karya Solutif - Adi Reski Surya Patioran; Avellyn Shinthya Sari; Muhammad Abdurrozak Siamashari; Ahmad Ubaidillah Fathoni; Ika Justitia Julita; Nazario Gomes (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2022)
In this study, the objective or focal point is the number of reserves that have been mined and how to calculate the volume mined using the Unmanned Aerial Vehicle (UAV) method. In the evaluation of the volume mined using the UAV approach in Tumiyang village, Kebasen sub-district, Banyumas regency, Central Java province, this research was conducted using qualitative and quantitative methods related to the characteristics and modeling of sediment distribution from prospect block exploration. This research was conducted in the even semester of the 2020-2021 academic year, which is between October 2020 to March 2021. Based on the results of the study, it can be concluded that the data collection process using the UAV method requires a short time and complete initial information regarding the condition of the research area is very important for success. aerial photography data collection. The data obtained is aerial photo data and with supporting data such as topography and geology. Based on data processing, the mined volume obtained using supporting software is 32,313.55 m3, while the volume obtained when we calculate manually is 247,050.65 m3.